--------------------------------------------------------------------------
Equation
--------------------------------------------------------------------------
![y - 9 = - \dfrac{1}{2} (x + 2)](https://tex.z-dn.net/?f=y%20-%209%20%20%3D%20-%20%20%5Cdfrac%7B1%7D%7B2%7D%20%28x%20%2B%202%29)
--------------------------------------------------------------------------
Rearrange the equation
--------------------------------------------------------------------------
![y - 9 = - \dfrac{1}{2} (x + 2) \\ \\ y - 9 = - \dfrac{1}{2}x - 1 \\ \\ y - 9 + 9 = - \dfrac{1}{2}x - 1 + 9 \ \Longleftarrow \text{add 9 to both side} \\ \\ y = -\dfrac{1}{2}x + 8](https://tex.z-dn.net/?f=y%20-%209%20%3D%20-%20%5Cdfrac%7B1%7D%7B2%7D%20%28x%20%2B%202%29%20%5C%5C%20%5C%5C%0A%20y%20-%209%20%3D%20-%20%5Cdfrac%7B1%7D%7B2%7Dx%20-%201%20%5C%5C%20%5C%5C%0A%20y%20-%209%20%2B%209%20%3D%20-%20%5Cdfrac%7B1%7D%7B2%7Dx%20-%201%20%20%2B%209%20%5C%20%5CLongleftarrow%20%5Ctext%7Badd%209%20to%20both%20side%7D%20%5C%5C%20%5C%5C%0A%20y%20%3D%20-%5Cdfrac%7B1%7D%7B2%7Dx%20%2B%208%20)
--------------------------------------------------------------------------
slope of the perpendicular line
--------------------------------------------------------------------------
slope = 2
(*the slope of the perpendicular line is the <span>
negative reciprocal of the slope of line)</span>
---------------------------------------------------------------------------
Substitute slope into equation y = mx + c
---------------------------------------------------------------------------
y = 2x + c
---------------------------------------------------------------------------
Find y-intercept
---------------------------------------------------------------------------
y = 2x + c
At point (0, 4)
4 = 2(0) + c
c = 4
----------------------------------------------------------------------------
Substitute y-intercept into the equation y = 2x + c
-----------------------------------------------------------------------------
y = 2x + 4
----------------------------------------------------------------------------
Answer: y = 2x + 4
-----------------------------------------------------------------------------